Phytoconstituents and diuretic activity of Cymbopogon citratus leaf infusions in humans - Ekpenyong, Christopher; Daniel, Nyebuk; Akpan, Ernest (Journal of coastal life medicine, 2014)
Objective: To assess the diuretic activity of infusions prepared from Cymbopogon citratus (C. citratus) leaves in healthy volunteers. Methods: One hundred and five subjects (55 men and 50 women) aged 18 to 35 years were randomly assigned to groups set to orally receive infusions prepared from 2, 4, or 8 g of C. citratus leaf powder, once daily for 30 d. Urine volume, frequency of urination, urine specific gravity, and plasma and urinary levels of electrolytes were assessed 1 day before (baseline), and at 10 and 30 d after initiation of treatment. Computed diuretic indices were compared between experimental and baseline values. Results: Subjects treated with infusions prepared from C. citratus leaf powder which tested positive for saponins, tannins, flavaniods, phenols, anthraquinones, alkaloids, and deoxy-sugar exhibited a significant increase in indices of diuresis including urine volume, urination frequency, diuretic action, natriuretic and saliuretic indices and renal fractional excretion of electrolytes and metabolic acidosis. A non-significant change in urine specific gravity was observed in all groups. eGFR showed a non-signific ant increase at Day 10, but decreased significantly (P<0.05) at Day 30. Thiazide and aldosterone secretion indices decreased at Day 10, whereas carbonic anhydrase index increased significantly (P<0.05) at both Days 10 and 30. Conclusions: These results indicate a loop active diuretic action of C. citratus infusion.